Evaluation of Internal Control Units for the Effectiveness of Financial Control in Administrative Government Units: A Field Study in Jordan - Al-Hawatmeh, Omar Mohammad; Al-Hawatmeh, Zaid Mohammad (European Scientific Journal, ESJ, 2016)
The aim of this study is to state the assessment of internal control units for the effectiveness of financial control in administrative government units. Also, it aims at identifying the obstacles that limits the evaluation of internal control units for the effectiveness of financial control in administrative government units. In order to achieve the objectives of the study and the testing of hypotheses, the researcher designed a questionnaire. This questionnaire was distributed to managers and employees in the internal control of the administrative government units. Out of the 125 questionnaires distributed, 96 were recovered with an adoption rate of 77%. The results showed that the assessment of internal control units for the effectiveness of financial control in administrative government units typically became high with an arithmetic mean (4.099) and standard deviation (0.511). The researcher attributed this result to the data analysis, verification, and validation of the financial transactions. Also, accounting entries which is related to income and expenditure were in accordance with laws, financial regulations, and the prescribed accounting for financial controls. Hence, this is the constraints that limit the effectiveness of the auditors of the Audit Bureau when they conducted financial and managerial control and evaluation in administrative government units. Generally, it became high with an arithmetic mean (3.551) and a standard deviation (0.610). Thus, the researcher attributed this result to the existence of certain obstacles, the most important routine work, lack of incentives and benefits, and others as indicated in the results of the study. Based on the results of the study, the researcher recommended the need for attention to the human element as one of the main components of internal control system. This is in terms of training and development to keep pace with scientific progress and the practical need to emphasize the reformulation of some legislation. Also, it helps with some of the aspects due to the need for harmonization between legislation. In addition, it helps with professional international standards, especially supreme control standards which give importance and effectiveness to financial control and other recommendations.